Labour Market Disadvantages of Citizens with a Migration Background in Belgium: A Systematic Review - Louise Devos; Louis Lippens; Dries Lens; François Rycx; Mélanie Volral; Stijn Baert (Institute of Labor Economics (IZA), 2024)
Labour markets struggle to be inclusive, while diversity is increasing. This literature review examines labour market challenges faced by first- and second-generation migrants in Belgium. We systematically review articles published between 2010 and 2023 in the Web of Science Core Collection to delineate underlying mechanisms, associated solutions, policy recommendations and literature gaps. The literature reveals that individuals with a migration background generally experience poorer labour market outcomes than natives. These outcomes vary based on specific origin and gender and persist from the first into the second generation. The mechanisms underlying these poorer outcomes are discrimination, individual preferences, and human and social capital differences. Recommendations for employers include implementing anti-discrimination policies, fostering awareness of discrimination, and taking affirmative action. On the employee side, investing in human capital, increasing labour market knowledge, and having competencies formally recognised can help to narrow employment gaps. Our review also advocates for policy refinement to combat biases and suggests that alternative pathways to attaining employment, such as self-employment and volunteering, are promising areas for future research.
Keywords: J15; J18; 330; Belgium; migration; labour market; systematic review